2016
DOI: 10.5812/ircmj.41043
|View full text |Cite
|
Sign up to set email alerts
|

Training Courses and Staff Knowledge for Implementation of High Reliability Organizations Model in Farabi Eye Hospital, Tehran, Iran

Abstract: Background: Hospitals as the most common health care centers should be changed into high reliability organizations to achieve the best performance and also improve patient safety. High reliability organizations can manage adverse events better, and create a safe environment for patients and staff. This requires accurate planning, training, and high responsibility and commitment hospitals leaders to implement this model. Objectives: The current study aimed to determine the knowledge of Farabi eye hospital's man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…These result were similar to those result obtained from other researcher who reported that total knowledge of staff about high reliability organizations model increased after training course (P<0.0001) [7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These result were similar to those result obtained from other researcher who reported that total knowledge of staff about high reliability organizations model increased after training course (P<0.0001) [7].…”
Section: Discussionsupporting
confidence: 92%
“…These results are accordance with findings obtained from other study, shows that after the training course, 47.5% of the respondents were somehow familiar with high reliability organizations model (HROs), and 52.5% admitted that they were completely familiar with this model, although, only 18.8% proved completely familiar with HROs model before the training course [7].…”
Section: Discussionsupporting
confidence: 91%
“…We identified 9 articles 6,18,23–29 that described 7 metrics for measuring progress toward becoming an HRO (Table 2). The Joint Commission’s HRHCM/Oro 2.0 stood out among the other metrics, as it involved broad stakeholder input in development, was validated by an external research team, covered all 5 of the most common implementation strategies, and was widely applicable.…”
Section: Resultsmentioning
confidence: 99%
“…[ 69 ] The special attention of managers and directors of medical laboratories to the individual and behavioral differences of their staff as a human resource management strategy has empowered their psychological, spiritual, and moral skill, and help them how to think and behave and decision making for organizational improvement. [ 70 71 72 ]…”
Section: Discussionmentioning
confidence: 99%